2021
DOI: 10.31254/jahm.2021.7107
|View full text |Cite
|
Sign up to set email alerts
|

Nature’s Anti-inflammatory agent and its use as a Local drug delivery agent for treatment of chronic periodontitis: A clinical, microbiological and biochemical study

Abstract: Periodontal disease can lead to progressive loss of tooth-supporting tissues and alveolar bone. Due to the clinical limitations of scaling and root planing and recolonization of bacteria, the use of systemic and local administration of antimicrobial agents as adjuncts seems beneficial. In recent years, herbal and ayurvedic remedies are being researched to treat common infections and inflammatory conditions. Here an attempt was made to evaluate the effect of curcumin 10mg (Curenext) (CU) used as an adjunct to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…This is due to the elimination of plaque and irritant factors by SRP results in a reduction of a BOP. This finding was in disagreement with studies done by Bhatia et al, Vijayapremakumar et al, and Pandy et al (5,9,10) which showed a significant difference in the BOP between groups.…”
contrasting
confidence: 82%
See 2 more Smart Citations
“…This is due to the elimination of plaque and irritant factors by SRP results in a reduction of a BOP. This finding was in disagreement with studies done by Bhatia et al, Vijayapremakumar et al, and Pandy et al (5,9,10) which showed a significant difference in the BOP between groups.…”
contrasting
confidence: 82%
“…Subjects who had used antibiotics or other medications in the previous three months, smokers, and pregnant or lactating women were excluded. The primary outcome in this study was the reduction in p.gingivalis and we determine the sample size by the use of https://gpower.software.informer.com/3.1/ Depending on the SD and mean of SD of p. gingivalis of test group (5) .…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation